Estimated glomerular filtration rate slopes on tenofovir alafenamide. Issue 9 (22nd July 2020) - Ibrahim, F; Campbell, L; Bailey, AC; Stockwell, S; Waters, L; Orkin, C; Johnson, M; Gompels, M; De Burgh‐Thomas, A; Jones, R; Schembri, G; Mallon, PW; et al.
Abstract : Objectives: The aim of the study was to analyse and compare estimated glomerular filtration rate (eGFR) slopes during exposure to tenofovir disoproxil fumarate (TDF) and tenofovir alafenamide (TAF) in individuals who initiated TAF, regardless of prior regimen, before October 2016. Methods: An observational cohort study was conducted at 11 clinics in the UK and Ireland. Mixed effects models with random intercept and time terms fitted were used to generate and compare eGFR slopes while participants were exposed to TDF and TAF, with adjustment for age, eGFR at TDF/TAF initiation, gender, ethnicity, and time‐updated CD4 cell count and HIV RNA measurements. Results: Data were available for 357 subjects (median age 50 years; 80% male; 82% white/other ethnicity; 51% men who have sex with men; median nadir CD4 count 216 cells/µL). The median duration of exposure to TAF was 2.0 (interquartile range 1.6, 2.3) years. At TAF initiation, the median CD4 count was 557 cells/µL, the median eGFR was 80 mL/min/1.73 m 2, and 86% had suppressed HIV infection. The mean adjusted eGFR slope during TDF and TAF exposure was −2.08 [95% confidence interval (CI) −2.24, −1.92] and 1.18 (95% CI 0.20, 1.52) mL/min/1.73 m 2 /year, respectively ( P  < 0.001). Individuals who experienced rapid eGFR decline (> 3 or 5 mL/min/1.73 m 2 /year) while receiving TDF experienced significant eGFR recovery while on TAF ( P  < 0.001). Conclusions: Significant improvement in eGFR slope was observed in patients who switched from TDF‐ to TAF‐containing antiretroviral regimens. These data provide further support for the renal safety of TAF, and for switching those who experience progressive worsening of renal function from TDF to TAF.